2021
DOI: 10.1021/acs.jpclett.1c00074
|View full text |Cite
|
Sign up to set email alerts
|

Raman Detection of Bond Breaking and Making of a Chemisorbed Up-Standing Single Molecule at Single-Bond Level

Abstract: Probing bond breaking and making as well as related structural changes at the single-molecule level is of paramount importance for understanding the mechanism of chemical reactions. In this work, we report in situ tracking of bond breaking and making of an up-standing melamine molecule chemisorbed on Cu(100) by subnanometer resolved tip-enhanced Raman spectroscopy (TERS). We demonstrate a vertical detection depth of about 4 Å with spectral sensitivity at the single chemical-bond level, which allows us not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…Moreover, of particular note is that during 2019–2021, a number of studies focused on chemical imaging with a resolution of a few angstroms (the chemical imaging of a single molecule or a single bond) were reported. 16,17,39,54–56 They are significantly different from TERS imaging studies before 2018, where the resolution was only at the nanometer level. Angstrom-resolved TERS microscopy, especially with the new scanning Raman picoscopy (SRP) methodology, can be used for visually constructing the chemical structure in real space and the determination of structural and chemical heterogeneities of surface species at the single-bond limit.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Moreover, of particular note is that during 2019–2021, a number of studies focused on chemical imaging with a resolution of a few angstroms (the chemical imaging of a single molecule or a single bond) were reported. 16,17,39,54–56 They are significantly different from TERS imaging studies before 2018, where the resolution was only at the nanometer level. Angstrom-resolved TERS microscopy, especially with the new scanning Raman picoscopy (SRP) methodology, can be used for visually constructing the chemical structure in real space and the determination of structural and chemical heterogeneities of surface species at the single-bond limit.…”
Section: Introductionmentioning
confidence: 85%
“…16 Wang et al reported the Raman detection of bond breaking and making of a chemisorbed up-standing single molecule at the single-bond level. 39 In situ nanospectroscopic imaging of plasmon-induced two-dimensional [4 + 4]-cycloaddition polymerization on Au(111) was reported by Shao et al 17 These three studies will be described in some detail later.…”
Section: Recent Development Of Ters Instrumentsmentioning
confidence: 95%
See 2 more Smart Citations
“…The combination of complementary spectroscopic information and topographic one provided by STM/AFM has shown its feasibility in this aspect (cf upper left panel of figure 9). For instance, application of tip-enhanced Raman spectroscopy (TERS) [166,167] and STM/AFM has been demonstrated to be capable of determining structural and chemical heterogeneities in the dehydrogenation processes at the single-bond limit [168] and identifying π-skeletons in coupling reactions [155], where the characteristic vibrational motions originated from specific bonds are the key to such chemical sensitivity. Moreover, TERS measurements have been shown to provide chemical information both laterally and vertically [167,168], which offer access to nonplanar stereo structures [167] and even more general 3D nanostructures.…”
Section: Discussionmentioning
confidence: 99%